DOI: 10.31274/etd-180810-4241
|View full text |Cite
|
Sign up to set email alerts
|

Production of activated carbon from fast pyrolysis biochar and the detoxification of pyrolytic sugars for ethanol fermentation

Abstract: Fast pyrolysis of red oak wood yields approximately 10-30 wt% biochar, considered a low value co-product. Production of high value activated carbon using steam was investigated at different activation conditions. The relationship between activation parameters, surface area, and revenue was evaluated using response surface methodology. A second-degree model showed a maximum economic benefit at 800°C with 5 minutes of steam activation, yielding $907 of net revenue per metric ton of biochar. Innovation Fast pyrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 102 publications
(179 reference statements)
2
14
0
Order By: Relevance
“…The physico-chemical characteristics and potential uses of adsorbent are greatly influenced by the biomass feedstock, feedstock pretreatments, carbonization method and activating conditions, such as temperature, gas type and reaction time [62]. Table 4 presents the contents of carbon, hydrogen, nitrogen, oxygen and ash content of the bioadsorbent.…”
Section: Chns/o and Ash Contentmentioning
confidence: 99%
“…The physico-chemical characteristics and potential uses of adsorbent are greatly influenced by the biomass feedstock, feedstock pretreatments, carbonization method and activating conditions, such as temperature, gas type and reaction time [62]. Table 4 presents the contents of carbon, hydrogen, nitrogen, oxygen and ash content of the bioadsorbent.…”
Section: Chns/o and Ash Contentmentioning
confidence: 99%
“…Abundant literature have examined the influence of activation parameters (e.g., activation temperature, activation time, gas flow rate, impregnation chemical, biochar ratio) on porosity development in activated biochars [24]. The results show that processing conditions at high activation temperature (e.g., 900 °C) [25][26][27][28][29][30][31], high CO2 or steam flow rate [32,33], longer residence time (e.g., 2h) [25,26,32,[34][35][36][37], and high chemical impregnation ratio [38][39][40] produce highly porous materials. However, little attention has been paid to the different pyro-gasification (i.e., an integrative term that comprises all thermochemical processes such as torrefaction, slow to fast pyrolysis, and gasification) conditions for biochar production or how these conditions affect the porosity of activated biochars.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is the highest value product analyzed in this study for biochar. Its selling price is between $1000 and $1500 per metric ton depending on the quality of the activated carbon 10 . The selling price used in this study was assumed to be $1100 per metric ton 7 .…”
Section: Value Of Co-product Alternatives For Biocharmentioning
confidence: 99%
“…With activated carbon the pores adsorb pollutants in either water or air waste streams. A study by researchers at Iowa State University found that converting biochar into activated carbon using steam is profitable 10 . Arena et al found that processing activated carbon from coconut shell instead of coal can greatly reduce the environmental burdens of activated carbon processing 11 .…”
Section: Introductionmentioning
confidence: 99%